Variety Of Second Singular Pronouns In Serawai Language - Nopriansah, Nopriansah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
NopriansahUniversity of Dehasen Bengkulunopriansahad@gmail.comÂ Â Â Abstract: This study focuses on the use of various second singular pronouns in Serawai language spoken in the village of Maras, the District of Seluma, Bengkulu Province, Indonesia. It aimed to provide a complete and valid description of the form, meaning, and context of various second singular pronouns in the language. The data were collected by using observational methods. The techniques applied in collecting the data were interview, reading some supporting literatures, recording the language production, and taking field notes. In analyzing the collected data, the researcher used the referential identity and distributional methods. While dividing the key factors, equalizing, differentiating, equalizing the main points, segmenting immediate constituents, substituting, and deleting are techniques applied in analyzing the data. By analyzing the forms, meanings, and functions of the objects, it was concluded that the two lexicons found were a variety of second singular pronouns in Serawai language. Whereas, the selection of using one of the variations was closely related to the social context of the speaker and the speech partner. The result of this study is expected to be useful for the development of linguistics.Keywords: form, meaning, variety, second singular pronouns, serawai language